A Review of Salmon Spawner-Recruitment Analysis: The Central Role of the Data and Its Impact on Management Strategy. Issue 3 (30th June 2022) - Adkison, Milo Douglas
Abstract: Management of anadromous salmon stocks is usually based on an estimate of the spawner-recruitment relationship. A wide variety of estimation approaches have been developed, from simple to complex, and some worthwhile methodologies and auxiliary data are underutilized. The types and quality of the data available determine the most appropriate assessment methodology and the reliability of the assessment results. The management strategies available and the performance of these strategies are likewise highly dependent on the available data. This review gives an overview of the range of assessment methodologies, from the ad-hoc to hierarchical Bayesian state-space approaches. It emphasizes the central role of data; data types, data deficiencies, auxiliary information such as environmental indices, habitat characteristics, and similar stocks, and the effects of the data on the quality of guidance to managers.